The effect of oral contraceptives on aromatase and Cox-2 expression in the endometrium of patients with idiopathic menorrhagia or adenomyosis - Maia H Jr; Haddad C; Pinheiro N; Casoy J (Dove Medical Press, 2013)
Hugo Maia Jr,1–3 Clarice Haddad,3 Nathaniel Pinheiro,4 Julio Casoy31School of Medicine, Federal University of Bahia, Salvador, Bahia, Brazil; 2Itaigara Memorial Day Hospital, Salvador, Bahia, Brazil; 3CEPARH (Centro de Pesquisas e Assistência em Reprodução Humana), Salvador, Bahia, Brazil; 4Imagepat Pathology Laboratory, Federal University of Bahia, Salvador, Bahia, BrazilBackground: The presence of aromatase and cyclooxygenase-2 (Cox-2) expression was investigated in the endometrium of patients with idiopathic menorrhagia or adenomyosis. The effect of oral contraceptives administered in extended regimens on the endometrial expression of these enzymes was also investigated.Methods and results: Aromatase expression was detected by immunohistochemistry in the endometrial glands and stroma of patients with idiopathic menorrhagia or adenomyosis. There was no difference in the percentage of aromatase expression in the endometria between the two groups. The mean intensity of Cox-2 expression in the glandular epithelium also did not differ significantly between the groups. Among the patients using oral contraceptives in extended regimens, the relative decrease in both aromatase and Cox-2 expression was significantly greater in amenorrheic patients compared with those who were experiencing breakthrough bleeding.Conclusion: The presence of aromatase expression in the endometrium is associated with the occurrence of menorrhagia, irrespective of the presence of adenomyosis. Continuous expression of these enzymes in the endometrium of users of oral contraceptives in extended regimens is positively associated with the presence of breakthrough bleeding. This suggests a role for both aromatase and Cox-2 in the etiology of abnormal uterine bleeding.Keywords: menorrhagia, aromatase, endometrium, Cox-2, adenomyosis